Sobre meninos e lobos: as personagens e o gênero policial na literatura e no cinema - Campos, Joana Bertani de (2020)
The purpose of this research was to establish a comparative analysis between the novel Mystic River, written by the American writer Dennis Lehane, and its cinematographic transposition, launched in 2003anddirected by Clint Eastwood. The main objectives of this study were to identify and establish elements of the crime fiction genre in literary work, as well as in film transposition; explore references on the theory of adaptation, intermidia, more specifically the relationship between literature and cinema, as well as elements of film analysis, in order to contribute to the discussion proposed in this dissertation; raising character studies and theories in literature and cinema to contribute to the analysis of six characters from both works: Sean, Jimmy, Dave, Lauren, Annabeth and Celeste, investigating how each of them is constructed in the novel and the movie. As a justification for this research, there is a lack of researches related to the film and the literary work and, above all, to the contribution tothe field of interart studies. Regarding the crime fiction genre, the studies of Todorov (1970 [2013]), P.D. James (2009 [2012]), Boileau and Narcejac (1995), Link (2002) and Massi (2011) were essential. For discussions regarding to Intermediate Studies,Interartes, adaptation theory and film analysis, studies by Clüver (2006; 1997), Hutcheon (2013), Stam (2006), Leitch (2003), Bazin (2011), Metz (1980) , Carrière (2006), Vanoye and Goliot-Lété (2012) and Bordwell and Thompson (1995) were of great relevance. On the other hand, on the construction of the characters, names such as Candido (2011), Gomes (2011), Brait (2017) and Forster (2015) were used as the theoretical basis for the analysis in question.